An assessment of the optimum timing of coastal flood adaptation given sea‐level rise using real options analysis. (4th October 2018) - Kim, Myung‐Jin; Nicholls, Robert J.; Preston, John M.; de Almeida, Gustavo A. M.
Abstract : There is large uncertainty about the changing magnitude and occurrence of coastal flood events with sea‐level rise; which poses significant challenges to adaptation planning. Recent decision‐making employs flexible options that can be modified/adjusted over time to address uncertainty. This research analyses a real option based method for assessing adaptation investment timing under coastal flooding and sea‐level rise. This method recognises and values the flexibility of waiting as an additional adaptation option under an uncertain future, that is, the key question concerns when the option is best implemented? Real options are applied using a test‐case in Lymington (UK), a floodprone coastal town. Our findings show that the option value (i.e., the net value of the overall benefit minus cost) grows with rising sea level to a maximum, which is the optimal time for the adaptation investment. The optimum investment time tends to occur at the same magnitude of sea‐level rise (relative to 1990) across most sea‐level rise scenarios for the same socio‐economic scenario. Hence, monitoring sea‐level rise provides important information to plan adaptation. The analysis provides an analytical framework on how and when to implement the adaptation option given the various future scenarios which can be developed further.